Pengaruh Struktur Organisasi Terhadapkomunikasi dalam Tim Audit - Rifqi Muhammad (Jurnal Akuntansi dan Auditing Indonesia, 2005)
Some audit researchers suggest that high levels of audit team structure may encumber communication within audit teams by impeding information-gathering activities. Others suggest that structure benefits communication by coordinating controlling information flows. This study evaluated these arguments by examining the relationship between the structure of audit teams and selected communication variables (information overload, boundary spanning, satisfaction with supervision, and accuracy of information). Questionnaire data were gathered from auditors from local and national public accounting firms with 49 auditors responding processed. Only accuracy of information have significant relationship with organization struc¬ture and the others only have negative relationship. The implication is that the level of structure adopted by teams has both posi¬tive and negative effects on communica¬tion, with structured teams providing greater control over information overload but impairing satisfaction with supervision and the accuracy of information.This research support Rudolph and Walker (1998) research that find the negative rela¬tionship of audit team structure variable and communication within audit team variables (informa¬tion overload, boundary spanning, satisfaction with supervision, and accuracy of information) although the results are not all significant like their research.Keywords: organizational structure, audit structure, communication, audit teams